2020
DOI: 10.1038/s41467-020-17108-5
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing ion leaching effects for achieving high oxygen-evolving performance on hybrid nanocomposite with self-optimized behaviors

Abstract: Ion leaching from pure-phase oxygen-evolving electrocatalysts generally exists, leading to the collapse and loss of catalyst crystalline matrix. Here, different from previous design methodologies of pure-phase perovskites, we introduce soluble BaCl 2 and SrCl 2 into perovskites through a self-assembly process aimed at simultaneously tuning dual cation/anion leaching effects and optimizing ion match in perovskites to protect the crystalline matrix. As a proofof-concept, self-assembled hybrid Ba 0.35 Sr 0.65 Co … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 149 publications
(101 citation statements)
references
References 54 publications
(120 reference statements)
4
88
0
Order By: Relevance
“…The Tafel plots in Figure 3d show that the NiFeMo-SR has a smaller Tafel slope of 32 mV dec −1 compared with those of the NiFeC-SR (35 mV dec −1 ) and IrO 2 (79 mV dec −1 ), verifying its superior catalytic kinetics. This OER performance is among the best for TM-based LDHs and also superior to those of most recently reported non-precious OER catalysts in alkaline media (Figure 3f and Table S1, Supporting Information), such as NiFe-LDHs, [45] NiFeO x H y , [46] hybrid BiCrCoFeO, [47] and Mo 2 C/Mo 2 N catalysts. [48] We estimated the electrochemically active surface area (ECSA) for two reference catalysts before and after ECSR activation by using double-layer capacitance (C dl ) from CV curves in the range of no Faradaic dynamics (Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 50%
“…The Tafel plots in Figure 3d show that the NiFeMo-SR has a smaller Tafel slope of 32 mV dec −1 compared with those of the NiFeC-SR (35 mV dec −1 ) and IrO 2 (79 mV dec −1 ), verifying its superior catalytic kinetics. This OER performance is among the best for TM-based LDHs and also superior to those of most recently reported non-precious OER catalysts in alkaline media (Figure 3f and Table S1, Supporting Information), such as NiFe-LDHs, [45] NiFeO x H y , [46] hybrid BiCrCoFeO, [47] and Mo 2 C/Mo 2 N catalysts. [48] We estimated the electrochemically active surface area (ECSA) for two reference catalysts before and after ECSR activation by using double-layer capacitance (C dl ) from CV curves in the range of no Faradaic dynamics (Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 50%
“…Recently, Wang et al suggested that the change of CN for metal atoms from EXAFS data could be helpful in the analysis of the defect concentration 60 . The fitting of CN from EXAFS data has been successfully reported in our previous study 63 . Based on the knowledge, we introduce a concept, the relative concentration of defects (RC d ), to perform a quantification analysis.…”
Section: Resultsmentioning
confidence: 95%
“…S11. Because the mixture phase has less ORR activity than Ag 2 Al with abundant oxygen species, and the ORR response would tend to be stable after the residual Al removed to form the stable intermetallic compound Ag 2 Al under the biased condition, which could be considered as a self-optimized behavior [43]. Also, this is an evidence that the intermetallic Ag 2 Al could contribute to ORR activity.…”
Section: Nanoporous Ag 2 Al For Orrmentioning
confidence: 99%